Insights for Japanese Teaching: A Contrastive Analysis of Jikan Kankaku (Time Consideration) between Japanese and Indonesia - Widianti, Susi; Ferian, Gia Oktavarel (Dirasat: Human and Social Sciences, 2026)
Objectives: Time consideration (jikan kankaku) is an act of considering the time when waiting for someone in a place. It is used to consider how long it will take for the person to arrive and decide if the person is late beyond the promised time. This study aims to discover the similarities and differences in time considerations between Japanese and Indonesians in certain situations. Methods: The method used in this research is a qualitative method with a comparative study. Data collection techniques used open-ended questionnaires and interviews with Japanese and Indonesian informants. The participants in this study were 39 Indonesians and 20 Japanese. Results: The results of this study show that most Japanese and Indonesians give time consideration of about 15 minutes to 30 minutes, depending on the individual. In Indonesia, arriving late is common, but it's not so common in Japan. Conclusion: In Japan, it is considered a virtue to arrive earlier than their appointment time. While Japan's monochronic culture is still deeply rooted today. In Indonesia, some people are still accustomed to a polychronic culture and tolerate someone's late arrival to give consideration to time. However, in certain situations, Indonesian people will also try to arrive at least 5 minutes before the appointment time to avoid being late.